1984
DOI: 10.1002/bjs.1800711128
|View full text |Cite
|
Sign up to set email alerts
|

A controlled trial of bipolar electrocoagulation in patients with upper gastrointestinal bleeding

Abstract: We have assessed the value of the BICAP electrocoagulation probe in reducing the incidence of further bleeding in patients with upper gastrointestinal haemorrhage. One hundred and twenty-nine patients were studied in a prospective randomized controlled trial. There were 85 male and 44 female patients, age range 16-92 years. Forty-five patients had stigmata of recent haemorrhage (visible vessel or spot) and were randomized during endoscopy to 24 control and 21 treatment patients. Seven control patients rebled c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1986
1986
2005
2005

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Efron [(1993), Section 5] studied an example of combining independent studies. The example concerns a randomized clinical trial studying a new surgical treatment for stomach ulcers [Kernohan, Anderson, McKelvey and Kennedy (1984)] in which there are 9 successes and 12 failures among 21 patients in treatment groups, and 7 successes and 17 failures among 24 patients in the control group. The parameter of interest is the log odds ratio of the treatment.…”
Section: Examplesmentioning
confidence: 99%
“…Efron [(1993), Section 5] studied an example of combining independent studies. The example concerns a randomized clinical trial studying a new surgical treatment for stomach ulcers [Kernohan, Anderson, McKelvey and Kennedy (1984)] in which there are 9 successes and 12 failures among 21 patients in treatment groups, and 7 successes and 17 failures among 24 patients in the control group. The parameter of interest is the log odds ratio of the treatment.…”
Section: Examplesmentioning
confidence: 99%
“…Other series have not been as positive [70]. A randomized trial [71] in a group of patients with ulcers displaying SRH showed no benefit in terms of rebleeding, surgery, transfusion, or mortality. The authors also noted difficulty in accessing 50% of the lesions, although others have found BICAP easier to apply, even tangentially [69].…”
Section: Bipolarmentioning
confidence: 99%
“…However, because of tissue adhering to the probe, it can incite further bleeding, and the depth of tissue burn cannot be well controlled. Bipolar cautery has recently been used for GI bleeding [67,68]. With this technique the current runs only at the tip of the probe and not through the patient to a ground, as with monopolar cautery.…”
Section: Medical Therapymentioning
confidence: 99%